A comparative study of operations of liquids in Barwe and Central Shona. Issue 2 (3rd May 2016) - Mangoya, Esau; Mheta, Gift
ABSTRACT: One universal characteristic of a language is that it has particular speech sounds that are organised and governed by rules. This article presents an analysis of functions and operations of liquids in Barwe. Barwe is a variety of Eastern Shona, a cross-border language spoken in Zimbabwe and Mozambique. The article draws comparisons between liquids in Barwe and those that obtain in Central Shona dialects, mainly Zezuru, spoken in and around Zimbabwe's capital Harare, and Karanga, which is spoken in the Masvingo and Midlands provinces of Zimbabwe. Liquids are found to occur in all the varieties that constitute the Shona group. According to Trask (1996), liquid is a conventional label for any non-nasal sonorant. In this paper, added focus is on three sounds which are: the lateral [l], the flap [ɾ] and the trill [r]. We thus make a comparative study of the laterals as they operate in Barwe and Central Shona. A phonological comparative analysis aids us in identifying the sound operations in the two varieties under discussion. The comparative study is conducted through analysis of corpora of these varieties which are in written and audio form. The phonological data are analysed using Kiparsky's (1982) Lexical Phonology Theory, which accounts for the systematic organisation of sounds in languages.